Influenza C Virus and Human Metapneumovirus Infections in Hospitalized Children With Lower Respiratory Tract Illness. Issue 11 (November 2015) - Shimizu, Yukitoshi; Abiko, Chieko; Ikeda, Tatsuya; Mizuta, Katsumi; Matsuzaki, Yoko
Abstract : A 6-month prospective study in a hospital setting detected influenza C virus and human metapneumovirus in 10.0% (29/289) and 16.6% (48/289), respectively, of children hospitalized with lower respiratory tract illness. Influenza C virus infection had a similar rate of pneumonia (53.3% vs. 57.1%), significantly lower frequency of wheezing (13.3% vs. 68.6%) and higher values of white blood cell and C-reactive protein than human metapneumovirus infection. Abstract : Supplemental Digital Content is available in the text.